Servant Issue in Virginia Woolf’s To The Lighthouse: A Journey From Marginalization to Inclusion - Babar Jamil, Muhammad; Hanif, Saba; Mubashir, Juvaria (Pakistan Languages and Humanities Review, 2022)
This study engages itself with an important social matter that gained intensity in the 1920s: servant issue, and reconsiders the interrelations between masters and the servants. Through exposing the kitchen and domestic labor, Woolf criticizes the social system constructed on the basis of one class exploiting the other. To battle with the hierarchical relationship between servants and masters, Woolf betrays a consciousness of more equality in class relations, which is generally juxtaposed and interlocked with gender equality in her texts. This study is rereading of the domestic party scenes in view of the emphatic moment of the cook’s spatial transgression from the kitchen to the drawing room, at which Woolf scrutinizes what has been hidden from the architecture of the Victorian private life.